Juridical Analysis OF Commando Accountability in Law No 26 of 2000 Concerning Human Rights Court - Suwito Suwito; Zonita Zirhani Rumalean; Wahyudi BR; Julisa Aprilia Kaluku (IHSA Institute, 2022)
Command responsibility is essential in international human rights enforcement, namely the 1998 Rome Statute. This is also regulated in Article 42 of Law No. 20 of 2000 on the Human Rights Court. Along the way, there are several areas for improvement in Law No. 20 of 2000 concerning the Human Rights Court, namely mistranslations, interpretations and unclear norms relating to command responsibility. This study aims to: (1) To be able to identify and analyze the Command Responsibilities in Law No. 26 of 2000; and (2) To be able to find out and analyze the comparison of Law No. 20 of 2000 on the Human Rights Court and the 1998 Rome Statute of command responsibility. This research is classified as normative research with a philosophical and analytical approach. Materials are collected through document studies and then analyzed prescriptively. The study results show that the Command Accountability in Law Number 26 of 2000 concerning the Human Rights Court has several weaknesses, interpretations and unclear norms related to command responsibility. Therefore, it is necessary to synchronize the 1998 Rome Statute with the Elaborated Approach, namely by adopting the provisions in the Rome Statute, which are elaborated with the National Legal Interest.